Investigating privacy perceptions, attitudes and behaviours of the inflammatory bowel disease online health communities - O'Leary, Kate (2021)
During their lifetime, people living with Inflammatory Bowel Disease (IBD) may require social support. Over the past 3 decades the internet has provided new opportunities for people living with chronic health conditions to meet virtually to both seek and receive empathetic support from the comfort of their own homes. Furthermore, the prevalence of smart mobile devices and social media platforms has provided individuals with easy to reach, on the go social support to meet their needs. Online support has been recognised as having additional benefits to face to-face support, such as how the asynchronous nature of online communications affords individuals to browse a rich history of previous posts. However, self-disclosed information on the internet is subject to privacy risks. In Law and Sociology, health information is considered to be ‘sensitive’ data; however, there are thousands of individuals living with IBD sharing intimate health information on social media platforms. This thesis explores how people living with IBD perceive their privacy on social media through a dual lens of social privacy and information privacy. A mixed-methods approach was adopted across 3 empirical studies to examine the perceptions, attitudes, and behaviours of people living with IBD and using social media to participate in online health communities. The first study explored how people living with IBD use Facebook, Twitter, and Instagram to engage with online health communities through 38 semi-structured interviews. The findings indicate that each of the platforms shared similar functionality which in turn generally afforded similar therapeutic outcomes. The analysis found evidence to suggest that people’s experiences of each platform was not exclusively as a result of the technical functions of each platform but were combined with their motivations and their previous social interactions. Significantly, this study also drew a distinction in the ways in which people perceive privacy on social media; demonstrating clear understandings of their social privacy boundaries and the actions they take to reduce privacy violations. Conversely, participants demonstrated a low awareness of how their data is collected and used by social media platforms, thus making it difficult for individuals to identify information privacy risks. The second study involved community leaders participating in focus groups to discuss the privacy challenges as well as identifying possible prototypes to support the digital well-being of potentially vulnerable people. Finding that an education-driven approach would be a suitable short-term option to improve people’s understanding, an intervention was developed through Patient and Public Involvement for the third study. The final study involved pre and post web-surveys to digital interventions to assess people’s attitudes towards learning more about online privacy, as well as its impacts on the IBD community. Taken together, this thesis presents new evidence to suggest how individuals use different social media platforms. It also demonstrates how social privacy and information privacy are thought and acted upon in different ways. However, there is some evidence to suggest that over the course of data collection for this PhD 4 (2017-2020) there are changing attitudes towards information privacy and the ways in which people’s health information is used by social media platforms.